Respostas
respondido por:
8
Olá,
m⁰ × m × m³
Mesma base, soma-se os expoentes:
m⁰ × m¹ × m³ = m⁰⁺¹⁺³ = m⁴
Resposta:
m⁴
m⁰ × m × m³
Mesma base, soma-se os expoentes:
m⁰ × m¹ × m³ = m⁰⁺¹⁺³ = m⁴
Resposta:
m⁴
Lauramartins11:
muito obrigado
respondido por:
5
m⁰ . m . m³
==
Todo numero ou incógnita elevado a zero é igual a 1
1 . m . m³
m . m³
=> m⁴
==
Todo numero ou incógnita elevado a zero é igual a 1
1 . m . m³
m . m³
=> m⁴
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás